Supervisi Akademik dengan Pendekatan Kolaboratif untuk Meningkatkan Mutu Lulusan: Studi Kasus di Madrasah Ibtidaiyah Miftahul Ulum Kecamatan Serpong Utara Kota Tangerang Selatan - Jamilah Muryati; Aris Munandar; Naufal Hilmizen; Agus Mulyanto; Waska Warta (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study examines the implementation of collaborative academic supervision at Madrasah Ibtidaiyah Miftahul Ulum, North Serpong District, South Tangerang City, as a strategy to enhance teaching quality and graduate outcomes. Collaborative academic supervision was conducted based on the management principles proposed by Terry (2021), namely planning, organizing, directing, and controlling. Data were collected through interviews, observations, and documentation, and analyzed using the Atlas.ti 9 software to generate a network view visualization illustrating the relationships among key supervision categories, such as understanding, process, participation, obstacles, evaluation, and benefits. The results indicate that this supervision significantly improved teacher performance, the variety of teaching methods, the use of technology, and student engagement in learning. The evaluation revealed an increase in teacher ratings from 54.5% rated B and 45.5% rated A in the first semester to 27.3% rated B and 72.7% rated A in the subsequent semester, reflecting a 27.27% improvement from B to A. This supervision also fostered a conducive, innovative, and student-centered learning environment, enhancing community satisfaction with the quality of education. This study recommends collaborative supervision as an effective approach to support the implementation of the Kurikulum Merdeka in madrasahs.